ZPA Flank Evaluation Using Spherical Stylus. (2016) - Albu, Sorin Cristian; Pozdîrcă, Alexandru
Abstract: The article presents a solution to control worms flank ZPA using stylus with spherical top on a coordinate measuring machines. The method allows evaluation axial profile deviation of the ZPA worms to nominal profile. We consider X axis of symmetry of a ZPA worm and XY its axial plan. A control sphere has its center in the XY plane chosen. It is necessary to impose share Y center of the sphere. It requires determining the X coordinate of the center sphere to sphere is tangent to the worms flank ZPA. The contact between the sphere and the helical surface of flank ZPA worms is a point which generally not belong XY axial plane chosen. Using the method of mutual winding surfaces can be determined parametric equations ZPA worm flank. ZPA flank worms ZPA is represented by a helical surface non-ruled. Point of contact between a sphere and the helical flank can be determined by numerical iterations based on a predetermined calculation error. These iterations are based on AutoLISP program developed by the authors, which allows verification of the results in AutoCAD graphics. By running the application AutoLisp, X nominal values can be determined, which is expected tangency of spherical stylus of a 3D Coordinate measuring machines and flank of ZPA worm. By comparing the X measured values with nominal value, execution errors of ZPA worm can be evaluated on coordinate measuring machines. The contributions are numerical calculation of the tangency position determination of a sphere and flank worm ZPA, designing an AutoLisp program for evaluation the position tangency of, creation an evaluation method of executed profile deviations compared to the nominal profile of the worm ZPA.